Pengembangan Sistem Rekruitmen Karyawan Perusahaan Mitra UPT Kewirausahaan Dan Pengembangan Karir Universitas Lampung - Destian ade anggi Sukma; Machudor Yusman; Favorisen Lumbanraja; Rico Andrian (Universitas Lampung, 2020)
Recruitment is the process of finding and the best-qualified candidate work in a company or agency. There are various recruitment methods such as via employee recommendations, university collaboration, job vacancy, and jobsfair. In this paper an online company employee recruitment will be made using the black box testing method with the Equivalence Partitioning technique and the Likert scale. The data is taken from company users and job seekers. System displays job vacancies in accordance with the minimum level of education, gender and applicant's GPA. Job seekers fill out the Curriculum Vitae (CV) on the system as a company assessment for acceptance of applicants.The system can also provide announcements for applicants who have successfully passed a company. The system has been tested with black box testing with technique Equivalence Partitioning and get valid results for each test case, and for testing using a Likert scale gets very good results with a value of 87.05%.